MEDICINA DE ESTILO DE VIDA Y RIESGO DE DESARROLLAR DIABETES MELLITUS EN PERSONAL DE LA CLÍNICA GOOD HOPE, LIMA – PERÚ, 2017. - Mamani-Espinoza, Fidel Raí (2018)
Abstract   Diabetes is a chronic disease that occurs when the pancreas does not produce enough insulin or when the body does not use efficiently the insulin it produces. According to the ENDES 2013, it has found a prevalence of overweight of 33.8% and obesity of 18.3%. Objective: Determine the results of the risk test for diabetes mellitus type 2 of the American Diabetes Society in the care and administrative personnel of a particular clinic. Methods: Observational, cross-sectional, analytical study that evaluates the probability of workers suffering from diabetes mellitus. The population of the study will be made up of workers, both clinical and administrative staff of the institution. Results: 34% of the population had normal BMI, 49% were overweight and 18.3% were obese. 15% of the studied population is at risk of developing diabetes mellitus type 2 according to the risk test for diabetes mellitus type 2 of the American Diabetes Society. The factors significantly associated with the risk of developing diabetes were older than 40 years OR: 10,14 IC95% 4,29, 23,98, p: 0.000; male sex OR: 2,35 % 1,06-5,21, p: 0.03; family history of diabetes OR: 6,330 IC95% 2,76-14,51, p: 0.000; BMI greater than 25 OR: 19,706 IC95% 2,62-147,96, p: 0.000 and physical activity OR: 28,95 IC95% 3,86-217,18; as well as the diagnosis of arterial hypertension OR: 13.500 IC95% 4.87-37.38. Conclusion: The risk found to develop diabetes was 15%, being higher in the administrative group than in the healthcare group. The factors associated with the risk of developing diabetes are directly linked to lifestyle medicine. Key words: Diabetes Mellitus; Risk Factors; Massive Screening. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1264